Effective Website Development Model for MSMEs to Encourage Innovation in Smart Cities - Ridho Pamungkas; Dimas Setiawan; Mei Lenawati; Bayu Saputra (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in the Indonesian economy. However, many MSMEs face obstacles in accessing digital technology to improve competitiveness and innovation. With the development of the Smart City concept, which integrates technology to improve quality of life and access to public services, MSMEs in areas that adopt it have the opportunity to utilise digital technology. Madiun City, as part of the Smart City initiative, has great potential in developing an inclusive digital ecosystem for MSMEs. This research aims to formulate an effective website development model for MSMEs in Madiun City, to support product innovation and marketing and improve competitiveness in the digital market. The analysis shows that website development can improve MSME competitiveness and innovation, with benefits such as wider market access and integration with digital marketing technology. However, the main challenges faced are limited digital knowledge, development costs, and security threats. Therefore, support from the government and related institutions is needed to provide training and resources for sustainable website management.